Development of trilayered mucoadhesive tablet of itraconazole with zero-order release - Madgulkar, Ashwini; Kadam, Shivajirao; Pokharkar, Varsha (Asian Journal of Pharmaceutics (AJP), 2014)
Itraconazole is practically insoluble in water; large interindividual and intraindividual variations of its oral bioavailability are reported. A mucoadhesive drug delivery system is useful to prolong the retention time of a dosage form in the stomach,thereby improving the oral bioavailability of the drug. Solid dispersion of itraconazole with Eudragit E100 was prepared by spray-drying method to improve dissolution. Trilayered mucoadhesive tablet was prepared, with inner core containing solid dispersion of the drug and with carbopol and HPMC sandwiched between two layers of hydrophilic mucoadhesive polymer mixture of carbopol and Hydroxypropyl methyl cellulose (HPMC). Amounts of Carbopol 934P (CP) and Methocel K4M (HPMC) were varied in the outer coat around the solid dispersion. The drug-release pattern for all the formulation combinations was found to be nonfickian, approaching zero-order kinetics. Suitable combination of two polymers provided adequate bioadhesive strength and sustained-release profile with zero-order kinetics.